Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1057/s41599-021-01013-3
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary approach to evaluate the impact of emotional dysregulation on adolescent decision making

Abstract: Evaluating decision-making during youth is a complex area of research. Multiple factors influence the young person’s subjective decision-making at this stage of development. Sub-optimal decision-making can have lifelong consequences. Longer adolescence, life stressors, drugs and alcohol and adverse events impact the young person, making them vulnerable to emerging mood disorders, such as anxiety and depression. Behavioural economics with its cognitive and multidisciplinary approach examines decision-making in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 103 publications
0
0
0
Order By: Relevance
“…These two forms of decision-making are often grouped as defensive-avoidant decision-making in the existing body of research (Mann et al 1997). Although evaluating decision-making during emerging adulthood has often been deemed a complex area of research informed by numerous factors (Weinrabe and Hickie 2021), previous studies have shown that young people were more likely to engage in buck-passing and procrastination decision-making (Kornilova et al 2018;Filipe et al 2020;Urieta et al 2021). Emerging adults in South Africa might have engaged in procrastination when making a decision or shifting the responsibility of making a decision as a result of the various challenges and hardships faced, such as chronic poverty, structural disadvantage and/or marginalization (Theron et al 2021a), which often hampers psychological health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…These two forms of decision-making are often grouped as defensive-avoidant decision-making in the existing body of research (Mann et al 1997). Although evaluating decision-making during emerging adulthood has often been deemed a complex area of research informed by numerous factors (Weinrabe and Hickie 2021), previous studies have shown that young people were more likely to engage in buck-passing and procrastination decision-making (Kornilova et al 2018;Filipe et al 2020;Urieta et al 2021). Emerging adults in South Africa might have engaged in procrastination when making a decision or shifting the responsibility of making a decision as a result of the various challenges and hardships faced, such as chronic poverty, structural disadvantage and/or marginalization (Theron et al 2021a), which often hampers psychological health and well-being.…”
Section: Discussionmentioning
confidence: 99%